Green Synthesis of Silver Nanoparticles by Plants Extract - Ahmed, Dina S; Mohammed, Teeba Hashim; Risan, Mohsen Hashim; Najim, Liqaa H; Mohammed, Salam A; Yusop, Rahimi M; Yousif, Emad (International Journal of Chemical and Process Engineering Research, 2019)
The development in the eco-friendly and cost-effective green synthesis of metal and semiconductor nanoparticles utilizing several natural resources like microorganisms, plant, flower and fruit extracts is an emerging area of nanotechnology. In recent years, the development of efficient green chemistry methods for synthesis of metal nanoparticles has become a major focus of researchers. One of the most considered methods is production of metal nanoparticles using organisms. Among these organisms plants seem to be the best candidates and they are suitable for large-scale biosynthesis of nanoparticles. Nanoparticles produced by plants are more stable and the rate of synthesis is faster than in the case of microorganisms. Moreover, the nanoparticles are more various in shape and size in comparison with those produced by other organisms. The advantages of using plant and plant-derived materials for biosynthesis of metal nanoparticles have interested researchers to investigate mechanisms of metal ions uptake and bioreduction by plants, and to understand the possible mechanism of metal nanoparticle formation in plants. In this review, most of the plants used in metal nanoparticle synthesis are shown. Researchers have focused their attention on understanding the biological mechanisms and enzymatic processes of nanoparticle biosynthesis as well as detection and characterization of biomolecules involved in the synthesis of metallic nanoparticles. Many biomolecules in plants such as proteins/enzymes, amino acids, polysaccharides, alkaloids, alcoholic compounds, and vitamins could be involved in bioreduction, formation and stabilization of metal nanoparticles. Genetic modification of plants with improved metal accumulation capacities is the future approach to increase the productivity of these organisms in nanoparticle synthesis.